Effects of yeast based toxin binder supplementation on growth performance and intestinal microarchitecture in male buffalo calves (Bubalus bubalis) exposed to different concentrations of Aflatoxin B1. - NASEER, O.; SALEEM, M. U.; SOHAIL, M. L.; NASEER, J.; KHAN, J.; OMER, M. O.; ANJUM, K. M.; AHMAD, A. S. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of study was to analyze the effects of yeast based toxin binder (YTB) on growth performance and intestinal microarchitecture of buffalo calves exposed to different concentrations of aflatoxin B1 (AFB1). Male buffalo calves (n=72) having no disease exposure in the last four months, aged 10 ± 1 months and weighing 150 ± 12.22 kg (Mean ± standard deviation)were purchased from a buffalo calf fattening farm and divided in 8 equal groups (n=9 animals in each group). Animals that were fed common basal diet and basal diet along with yeast cell wall based toxin binder (YTB) and had no exposure to AFB1 were served as controls. Different concentrations of AFB1 (6mg, 8mg and 10mg per kg of feed) were given to 27 animals, similarly 2mg of YTB (per kg of contaminated feed) was added to concentrate with different AFB1 concentrations and fed to another 27 animals. Average daily gain of each animal was recorded. Animals were slaughtered after 27 days and intestinal segments from duodenum, jejunum, ileum and colon were collected which were stained with hematoxylin/eosin or combined alcian blue and periodic acid schiff stain. Average daily gain and intestinal morphometric parameters (villus height, villus width, crypt depth and surface area) in all the selected intestinal segments decreased (P<0.05) whereas, intraepithelial lymphocytes, goblet cells (having acidic and neutral mucins) and proliferative cells increased (P<0.05) with AFB1 exposure. It was also observed that YTB neutralized (P<0.05) the harmful effects of AFB1 on intestinal morphology, boosted activity of goblet cells and decreased (P<0.05) number of proliferative cells. It was concluded that YTB supplementation is advantageous in eliminating the negative effects of AFB1 on gut of buffalo calves.